Autophagy: A new strategy for host-directed therapy of tuberculosis - Paik, Seungwha (Virulence, 2018)
Tuberculosis (TB), which is primarily caused by the major etiologic agent Mycobacterium tuberculosis (Mtb), remains a serious infectious disease worldwide. Recently, much effort has been made to develop novel/improved therapies by modulating host responses to TB (i.e., host-directed therapy). Autophagy is an intracellular catabolic process that helps maintain homeostasis or the removal of invading pathogens via a lysosomal degradation process. The activation of autophagy by diverse drugs or agents may represent a promising treatment strategy against Mtb infection, even to drug-resistant strains. Important mediators of autophagy activation include vitamin D receptor signaling, the AMP-activated protein kinase pathway, sirtuin 1 activation, and nuclear receptors. High-throughput approaches have identified numerous natural and synthetic compounds that enhance antimicrobial defense against Mtb infection through autophagy. In this review, we discuss the current knowledge of, advancements in, and perspectives on new therapeutic strategies targeting autophagy against TB. Understanding the mechanisms and key players involved in modulating antibacterial autophagy will provide innovative improvements in anti-TB therapy via an autophagy-targeting approach. Abbreviations: TB: Tuberculosis; Mtb: Mycobacterium tuberculosis; HDT: host-directed therapy; MDR: multidrug resistant; XDR: extensively drug resistant; LAP: LC3-associated phagocytosis; ROS: reactive oxygen species; VDR: vitamin D receptor; TFEB: transcription factor EB; ERRα: estrogen-related receptor α; PGC1α: PPARγ coactivator-1 α